Proposal of non-invasive experimental model to induce scoliosis in rats - Carlos A. Silva (Revista Brasileira de Fisioterapia, 2012)
Background: In the literature, there are several experimental models that induce scoliosis in rats; however, they make use of drugs or invasive interventions to generate a scoliotic curve. Objectives: To design and apply a non-invasive immobilization model to induce scoliosis in rats. Methods: Four-week old male Wistar rats (85±3.3 g) were divided into two groups: control (CG) and scoliosis (SG). The animals in the SG were immobilized by two vests (scapular and pelvic) made from polyvinyl chloride (PVC) and externally attached to each other by a retainer that regulated the scoliosis angle for twelve weeks with left convexity. After immobilization, the abdominal, intercostal, paravertebral, and pectoral muscles were collected for chemical and metabolic analyses. Radiographic reports were performed every 30 days over a 16-week period. Results: The model was effective in the induction of scoliosis, even 30 days afterimmobilization, with a stable angle of 28±5º. The chemical and metabolic analyses showed a decrease (p<0.05) in the glycogenic reserves and in the relationship between DNA and total protein reserves of all the muscles analyzed in the scoliosis group, being lower (p<0.05) in the convex side. The values for the Homeostatic Model Assessment of Insulin Resistance indicated a resistance condition to insulin (p<0.05) in the scoliosis group (0.66±0.03), when compared to the control group (0.81±0.02). Conclusions: The scoliosis curvature remained stable 30 days after immobilization. The chemical and metabolic analyses suggest changes in muscularhomeostasis during the induced scoliosis process.